2015
DOI: 10.1021/acs.analchem.5b00675
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Doped Liquid Crystal Sensor System for Detecting Mercuric Ion in Aqueous Solutions

Abstract: We developed a liquid crystal (LC) sensor system for detecting mercuric ion (Hg(2+)) in aqueous solutions. In this system, 4-cyano-4'-pentyl biphenyl (5CB) was doped with a sulfur- and nitrogen-containing ligand 5-(pyridine-4-yl)-2-(5-(pyridin-4-yl)thiophen-2-yl)thiazole (ZT) as the Hg(2+) specific LCs. When the system was immersed in the solution containing Hg(2+), the complex of ZT and Hg(2+) formed, which disrupted the orientation of LC and lead to a dark-to-bright transition of the image of LCs. From mercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…We are currently experiencing an increasing interest in gas sensors based on liquid crystals (LCs) [32][33][34][35][36][37][38][39][40][41], functioning at room temperature, requiring no energy supply as they are powered by thermal energy alone, and delivering a strong optical response that is easily detected without complex spectroscopic equipment. The response is due to the ability of certain gas molecules, even at low concentration, to strongly influence the liquid crystal self-assembly [40,[42][43][44][45], triggering a reorientation of the liquid crystal director [32,34,43,44], a change in period of the supramolecular helix of shortpitch cholesterics [19,36,42,[46][47][48], or even complete loss of long-range ordering [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are currently experiencing an increasing interest in gas sensors based on liquid crystals (LCs) [32][33][34][35][36][37][38][39][40][41], functioning at room temperature, requiring no energy supply as they are powered by thermal energy alone, and delivering a strong optical response that is easily detected without complex spectroscopic equipment. The response is due to the ability of certain gas molecules, even at low concentration, to strongly influence the liquid crystal self-assembly [40,[42][43][44][45], triggering a reorientation of the liquid crystal director [32,34,43,44], a change in period of the supramolecular helix of shortpitch cholesterics [19,36,42,[46][47][48], or even complete loss of long-range ordering [11].…”
Section: Introductionmentioning
confidence: 99%
“…In these cases the LC sensor response arises from an analyte-induced change of anchoring conditions, leading to a major change in director field geometry within the sample, which in turn results in a strong change in optical properties. Other researchers [37,38,41] have demonstrated alternative approaches for exploiting LCs as sensors to chemical agents, sensitised either through doping or other chemical modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Singh, et al [17] reported Selective detection of Hg 2+ up to 0.5 µM using thiocarbamate as a chemical probe. Similarly, Chen, et al [18] also detected Hg 2+ down to 10 µM using 5-(pyridine-4-yr)-2(5-(pyridine-4-yr)thiophen-yl) diazole. However, these molecular probes were chemically synthesized and used for the detection of a specific metal ion in water and have certain shortcomings such as the chemical synthesis of these probes being complicated; they also cannot be used for the detection and quantifications of heavy metal ions in body fluids.…”
Section: Introductionmentioning
confidence: 81%
“…Liquid crystals (LCs) have been widely applied to various fields, such as flat panel displays [1,2], electro-optical devices [3][4][5], biological [6,7] or environmental sensors [8,9], and topological defects [10,11] in a micrometer scale. Blue phase LCs (BPLCs) are among the most promising materials for advanced applications because of their superior characteristics, such as self-assembled three-dimensional (3D) photonic structure and fast response time [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%